ETHNOMATHEMATICS FROM PAST AND CURRENT USES: A DIDACTIC INFERENCE - Weldeana, Hailu Nigus; Leung, Frederick KS (Ethnomath Association in cooperation with Universitas Negeri Yogyakarta, 2025)
Over the past few decades, Ethnomathematics has drawn attention to the existence of culturally embedded mathematical knowledge systems; yet, their systematic pedagogical transfer into formal school mathematics is still limited in many African contexts, including Ethiopia. This study looks at Ethiopian ethnomathematical practices from historical and contemporary cultural activities in order to incorporate them into curriculum-aligned mathematical learning paths. Data was gathered utilizing a qualitative ethnographic approach using document analysis, field observations, artifact analysis, and semi-structured interviews with cultural practitioners and educators from specific Ethiopian communities. Analytical reconstruction was utilized to identify underlying mathematical structures in order to translate indigenous activities onto formal mathematical concepts such as geometry, measurement, slope, optimization, and spatial reasoning. The findings demonstrate how complex and cohesive mathematical ideas are embodied in Ethiopian cultural practices such as terracing, threshing floor design, traditional storage systems, embroidery patterns, and monument construction. These ideas can be carefully transformed into modeling exercises, classroom assignments, and inquiry-based projects. These reconstructions provide culturally relevant meditation methods in addition to enhancing conceptual understanding, leaner engagement, identity affirmation, and epistemic justice. By offering a theoretically informed framework for integrating indigenous knowledge into mathematics curricula and teacher preparation, the study advances socially relevant and culturally sensitive mathematics education in Ethiopia.